(untitled) - Goldstein, Beth. (New York, 2008)
The Ultimate Small Business Marketing Toolkit gives you the resources to do just that, with a wide variety of cost-effective marketing techniques you can use to turn your business vision into reality.
Keywords: marketing,small business,Quảng cáo; management,management,Quản trị quảng cáo